1980
DOI: 10.1038/hdy.1980.22
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal locations of highly repeated DNA sequences in wheat

Abstract: SUMMARYC0t l0 DNA was isolated from hexaploid wheat Tr-iticum aestivum cv. Chinese Spring by hydroxyapatite chromatography (70°C in 0l2 M phosphate buffer). The higher Tm of the Cot 10-2 DNA compared with total wheat DNA suggested that it was relatively GC rich and contained well matched hybrids.In situ hybridisation using wheat species of different ploidy levels located major sites of the C0t l0-DNA on the B genome chromosomes. More than one particular highly repeated sequence is located in these sites. Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…4). This pattern of sites is the same as that produced by a rapidly renaturing fraction (Gerlach and Peacock, 1979); presumably the individual chromosomal sites are also the same. No major sites were present on other A or D genome chromosomes; however, longer exposures (x 10) showed the presence of minor sites on both A and D genome chromosomes.…”
Section: _____supporting
confidence: 52%
“…4). This pattern of sites is the same as that produced by a rapidly renaturing fraction (Gerlach and Peacock, 1979); presumably the individual chromosomal sites are also the same. No major sites were present on other A or D genome chromosomes; however, longer exposures (x 10) showed the presence of minor sites on both A and D genome chromosomes.…”
Section: _____supporting
confidence: 52%
“…Species divergence in the diploids has not involved translocation of this sequence to telomeric regions but rather the changes in amount and position have been restricted to similarly located regions of all diploid genomes. This parallels the findings in wheat, rye and barley (Hutchinson and Lonsdale, 1982;Peacock et a!., 1981;Bedbrook et a!., 1980;Gerlach and Peacock, 1980). As suggested by Flavell (1982), such sequences are perhaps tolerated only at specific locations and their similar locations in nonhomologous chromosomes of the same genome may reflect on the mechanism by which they move between chromosomes.…”
Section: Discussior (I) Tc22b Probesupporting
confidence: 86%
“…Since the initial studies in V. faba by Vosa and Marchi in 1972, chromosomes of many species of Aegilops, Agropyron, Elymus, Hordeum, Secale, and Triticum (Gill and Kimber, 1974a and b;Linde Laursen, 1975;Vosa, 1976;Gerlach and Peacock, 1980;Singh and Tsuchiya, 1981b;Seal, 1982;Teoh and Hutchinson, 1983;Endo, 1986;Morris and Gill, 1987) and other plant species (Linde Laursen et al, 1980;Loidl, 1983) have revealed C bands. These studies show that there is a fundamental dif ference in the distribution of constitutive hete rochromatin within chromosomes of animals and plants.…”
Section: Bandingmentioning
confidence: 99%
“…These include some highly repetitive short base pair sequences in the chromosomes of animals (Pardue and Gall, 1970;Brutlag et al, 1977) and plants Appels and McIntyre, 1985;Ganal et al, 1988;Lapitan et al, 1989), moderately repeated sequences such as rRNA genes in the chromosomes of animals Steffensen, 1970, 1973;Henderson et al, 1972) and plants (Wimber et al, 1974;Gerlach and Bedbrook, 1979;Mascia et al, 1981;Clark et al, 1989), and some single copy genes in animals (Harper and Saunders, 1981;Henderson, 1982;Olsen el al., 1989) and plants (Ambros et al, 1986;Huang et al, 1988). Gerlach and Peacock (1980) isolated a highly repetitive DNA sequence from T. aestivum cv. Chinese Spring and hybridized it to cytological preparations of T. aestivum, T. dicoccoides, T. monococcum and Ae.…”
Section: N Bandingmentioning
confidence: 99%